Mediation of psychological capital between organizational climate and organizational citizenship behavior - Faisal Qadeer; Hina Jaffery (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Employees' psychological capital has important impacts on his/her job related as well as non-job related behaviors like organizational citizenship behavior (OCB). Organizational climate is one of the antecedents of psychological capital. The paper specifically attempts to investigate the mediation of psychological capital in organizational climate-OCB relationship through a survey of 108 employees of a multinational consulting organization. The results show that psychological capital is significantly related with both organizational climate and OCB towards a) organization and b) colleagues. However, no relationship is found between organizational climate and OCB in either form. Mediation analysis indicates that the impact of organizational climate on OCB is not direct; it is mediated by psychological capital such that OCB occurs only if supportive organizational climate is converted into employee psychological capital.
Keywords: 330; organizational climate; psychological capital; OCB; managerial trust